Indonesia's Digital Economy's Development - Dudhat, Amitkumar; Agarwal, Vertika (Pandawan Sejahtera Indonesia, 2023)
Digital technology must be used in all facets of life and business for global advancements to lead to the employment of technology in all disciplines, including the economic sector. One of the nations that quickly digitized their economy was Indonesia. The issue is whether Indonesia can foresee the effects and dangers that the digital economy will pose. This study's objective is to examine the growth of Indonesia's digital economy and the challenges it poses from the standpoint of national defence. The descriptive qualitative methodology is used in this study. Interviews with representatives from the Ministry of Communication and Information, the Ministry of Defense, and the Indonesian Coordinating Ministry for Economic Affairs provided the data, which was then supplemented with secondary information from these agencies. The study's findings show that Indonesia's digital economy is growing quite well, which boosts the country's GDP. They also show that productivity is rising, production, consumption, and distribution are moving more quickly, there is economic growth in various sectors, and the country can continue to operate despite the Covid-19 pandemic. The digital economy, however, also poses a threat to national security because digitization forces all data to be connected to servers that are vulnerable to data misuse and exploitation; transactions that are not secure from malware-based cyberattacks; fraudulent transactions or hacks by hackers; and infrastructure limitations that have not yet reached all parts of Indonesia